Isocrates and the Culture of Discourse - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2023)
In this article, I aim at presenting and commenting on a series of interesting ideas discovered in Isocrates’ ancient discourses, precisely those ideas referring to the importance of language for man in general, seen as a social being. In this regard, one should notice the specific meaning he gave to the Old Greek term philosophia, understood as ‘the culture of discourse’. In other words, I will try to prove that Isocrates’ rhetorical work deserves more appreciation from the specialists or researchers who deal with linguistic ideas and problems of philosophy of language.